2018
DOI: 10.1037/pspa0000129
|View full text |Cite
|
Sign up to set email alerts
|

Lean in messages increase attributions of women’s responsibility for gender inequality.

Abstract: Although women’s underrepresentation in senior-level positions in the workplace has multiple causes, women’s self-improvement or “empowerment” at work has recently attracted cultural attention as a solution. For example, the bestselling book Lean In states that women can tackle gender inequality themselves by overcoming the “internal barriers” (e.g., lack of confidence and ambition) that prevent success. We sought to explore the consequences of this type of women’s empowerment ideology. Study 1 found that perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 83 publications
3
65
2
Order By: Relevance
“…Another potential consequence of a purely gender-blind ideology, which disregards some of the unique challenges women face, could be to blame women for their disadvantaged position. That is, gender-blindness can, while being empowering, also enhance “victim blaming” (see Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Another potential consequence of a purely gender-blind ideology, which disregards some of the unique challenges women face, could be to blame women for their disadvantaged position. That is, gender-blindness can, while being empowering, also enhance “victim blaming” (see Kim et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our recent work has found that too much focus on the individual, rather than systemic, contributors to inequality may have pernicious consequences. Specifically, we found that exposure to individually focused messages which promoted women's empowerment to overcome ‘internal barriers’ (e.g., a lack of confidence and ambition) that prevent workplace success (e.g., to ‘lean in’; Sandberg & Scovell, ) led to increased attributions that women were responsible for both creating and solving the problem of gender inequality (Kim, Fitzsimons, & Kay, ). Collectively, these findings suggest that when the institutional‐level contributors to inequality are overlooked, potentially harmful individual‐level blame might occur.…”
Section: Introductionmentioning
confidence: 99%
“…The second implication from these results is that organizations’ investment in developing programs to retain women engineers need to move away from trying to “fix women” by asking them to lean in (Sandberg, 2013) or equipping women engineers with more self-confidence boosting skills to fixing the work environment that can better address their needs for comfort and status, just as it would for their male counterparts. Recent reports have suggested that strategies such as asking women to “lean in” not only fail to yield desired results, but in some cases backfire and lead to departure (e.g., Kim, Fitzsimmons, & Kay, 2018; Toosi, Mor, Semnani-Azad, Phillips, & Amanatullah, 2019). A third implication of this research is that while discorrespondence between the person and the environment can be addressed either by actively changing the work environment or by changing their own needs, employees may rationalize their needs as not being that important or reprioritize their important values.…”
Section: Discussionmentioning
confidence: 99%